Eficácia do laser cirúrgico de diodo no tratamento da hiperplasia fibrosa inflamatória - Marcio Bruno Figueiredo do Amaral (2014)
The objective of this study was investigated the efficacy of diode laser surgery in the treatment of inflammatory fibrous hyperplasia compared with conventional technique using a scalpel in randomized clinical trial. Thirty eight patients with inflammatory fibrous hyperplasia were evaluated. In the control group, patients were submitted to scalpel surgery; in the study group, patients were submitted to treatment with diode laser surgery. The patients of the study group were treated using an 808nm diode laser in a continuous mode, with a mean of potency of 2.96W. A numeric visual analogue scale was applied to assess the post-operative pain, functional alterations during speech and chewing and patient satisfaction with the treatment modalities. Additionally, type of anesthesia, needed of postoperative analgesic medicine, bleeding, post-operative edema and time of the surgery were assessed. The relationship between groups with post-operative pain and functional alterations was assessed by the U Mann-Whitney test. The relationship among groups with time of the surgery was assessed by student t test due to normal distribution of the data. Categorical variables were assessed by Chi-Square test or Fisher exact test. Thirty-four patients were analyzed in accordance with inclusion and exclusion criteria. The time of surgery was significantly minor in the study group (p= 0.04). The need of analgesic medicine in the post-operative period was significantly higher in the control group (p= 0.01). However, clinical healing of the post-operative wounds was significantly higher in the study group (p= 0.01). The diode laser surgery proved to be well-tolerated by patients reducing the needed of analgesic medicine in the postoperative period when compared with scalpel surgery. Furthermore, the diode laser surgery proved to be effective in the management of fibrous hyperplasia with minimal bleeding, less invasive avoiding sutures, and decreasing the time of surgery. Thus, diode laser demonstrated less invasiveness when compared with scalpel surgery. By contrast, wound healing proved to be faster with scalpel surgery when compared with diode laser surgery.